Emerging Roles of SIRT3 in Cardiac Metabolism - Murugasamy, Krishnega; Munjal, Aastha; Sundaresan, Nagalingam Ravi (Frontiers in Cardiovascular Medicine, 2022)
The heart is a highly metabolically active organ that predominantly utilizes fatty acids as an energy substrate. The heart also derives some part of its energy by oxidation of other substrates, including glucose, lactose, amino acids and ketones. The critical feature of cardiac pathology is metabolic remodelling and loss of metabolic flexibility. Sirtuin 3 (SIRT3) is one of the seven mammalian sirtuins (SIRT1 to SIRT7), with NAD+ dependent deacetylase activity. SIRT3 is expressed in high levels in healthy hearts but downregulated in the aged or diseased heart. Experimental evidence shows that increasing SIRT3 levels or activity can ameliorate several cardiac pathologies. The primary deacetylation targets of SIRT3 are mitochondrial proteins, most of which are involved in energy metabolism. Thus, SIRT3 improves cardiac health by modulating cardiac energetics. In this review, we discuss the essential role of SIRT3 in regulating cardiac metabolism in the context of physiology and pathology. Specifically, we summarize the recent advancements that emphasize the critical role of SIRT3 as a master regulator of cardiac metabolism. We also present a comprehensive view of all known modulators of SIRT3 activity and elaborate on their therapeutic potential to ameliorate energetic abnormalities in various cardiac pathologies.